Professionals’ perceptions on earnings management: the effect of demographic factors - De Silva, P.O. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2019)
An intentional manipulation of corporate financial data in order to achieve a specific objective, which is driven by market, contractual or regulative motive is introduced as Earnings Management. Therefore, this study attempts to pursue the professionals’ attitudes toward the ethical acceptability of earnings management practices and whether professional’s attitudes differ with their demographic characteristics. The professionals who work in the accounting and auditing sector were guided with thirteen difference earnings management scenarios which were adapted from Clikeman et al.’s (2000) study. Their responses for these 13 different scenarios were recorded with their demographic characteristics and SPSS 16 statistical package was used for the analysis.100 accounting/ auditing professional’s selected based on convenient sampling were given a scenario based Lickert scale questionnaire as aforementioned. The response rate was 90% where 53.3% were males and 46.7% females. 55.6% represented non- audit sector. 40% of participants were belonged to the middle layer of management hierarchy and 72.2% were in the age group of 21- 30 years. The research findings contribute to the literature that the perception of ethical acceptability of earnings management is not affected by demographic variables. The earnings management framework provides a sensible explanation of ethical acceptability of earnings management practices in Sri Lanka. The loopholes in the market operations, contractual obligations and regulations induce business entities to execute unethical earnings management practices. Therefore it is in need of an ethical framework.
Keywords: Earnings Management; Professionals; Demographic Factors